Integrasi Program Pencegahan HIV/AIDS melalui Transmisi Seksual ke dalam Sistim Kesehatan di Kota Kupang - Sir, Amelya Betsalonia (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2020)
Background: HIV and AIDS prevention efforts in Indonesia could not be denied that it is still influenced by global health initiatives. As global initiatives continue to decline, efforts to integrate HIV and AIDS programs into the framework of the national health system are both challenges and hopes for achieving program effectiveness and sustainability. This study aims to explore how far the integration of HIV transmission program through sexual transmission into the health system contributes to the effectiveness of programs at the Kupang City level. Method: The method used in this research is qualitative analysis with case study design as an effort to understand more deeply the relationship between the integration and effectiveness of AIDS prevention program. In this study the 'case' chosen was HIV prevention programs through sexual transmission for Female Sex Workers. Results: The results of the study showed that in the prevention of HIV transmission programs through sexual transmission as many as five sub-systems of health were partially integrated, including sub-systems of management and regulation, health financing, human resource management, provision of pharmaceuticals and medical devices and sub-systems for community participation management, while the strategic information sub sub-system is not integrated in the health system. The integration of some sub-systems into the health system does not contribute to the effectiveness of the program. Therefore, it was necessary to strengthen each sub-systim, especially in regions ranging from regulation, planning and budget including human resources to increase regional independence and not rely on foreign funds for the implementation of HIV prevention programs through sexual transmission, besides that it also increases collaboration with stakeholders.Â